Political economy, neoliberalism, and the prehistoric economies of Latin America - Matejowsky, Ty; Wood, Donald C. (Research in economic anthropology ;, 2012)
Volume 32 of REA continues the series' on-going presentation of new and highly engaging anthropological research. Chapters contained herein reflect the diverse range of broad based and localized topics economic anthropologists currently explore from various critical perspectives. Spanning deep history and present day economic processes, the contributions to this volume are subdivided into three major thematic sections. Part I addresses questions of how the political economy is articulated at the macro - and micro-level through processes of consumption, production, gift-giving, and evolution. The essays of Part II assume a more critical stance as outcomes of neoliberalism are considered from both a gendered and institutional perspective. Finally, the papers of Part III shift focus to the prehistoric economies of Latin America.